Web-Based Investor Fear Gauge and Stock Market Volatility: An Emerging Market Perspective. (August 2020) - Graham, Michael; Nikkinen, Jussi; Peltomäki, Jarkko
This article considers web-based global investors' crash fears as a gauge of global investors' fears, and examines its effect on stock market volatility in a sample of emerging stock markets. We show that an increase in global investors' crash fears significantly affects the volatility of stock index returns in emerging markets. The results are robust to the inclusion of the conventional investor sentiment/fear gauge measure, VIX. Thus broadening the set of measures of global investors' fears is important when explaining emerging market volatilities. JEL Classification: F30, G11, G15